化学的虚血による遅発性神経細胞死に対するノルアドレナリンによるアストロサイトを介した神経保護作用 - 石丸, 侑希; 若山, 太一; 高田, 綾香; 吉岡, 靖啓 (日本薬理学会年会要旨集, 2023)
In this study, we examined the effect of noradrenaline on delayed neuronal death induced by chemical ischemia, a model of ischemia-reperfusion injury in vivo, in the mixed culture of human astrocytoma U-251 MG cells and human neuroblastoma SH-SY5Y cells. Chemical ischemia was induced by incubating the cultures in buffered salt solution containing 0.5 mM 2-deoxy-D-glucose and 5 mM sodium azide for 3 hours. After the induction of chemical ischemia, the medium was replaced with DMEM and cultured for an additional 45 hours. Delayed neuronal cell death of SH-SY5Y cells after chemical ischemia was significantly attenuated by noradrenaline (3 μM) in the mixed culture, but not in single culture of SH-SY5Y cells. The neuroprotective effect of noradrenaline was inhibited by a nonselective α-adrenoceptor antagonist phenoxybenzamine (3 μM), but not by a nonselective β-adrenoceptor antagonist propranolol (10 μM), whereas a selective α1-adrenoceptor agonist phenylephrine (1-30 μM) attenuated chemical ischemia-induced cell death of SH-SY5Y cells in the mixed culture. These results suggest that noradrenaline attenuates chemical ischemia-induced delayed cell death of SH-SY5Y cells by stimulating the α₁ receptor of U-251 MG cells in the mixed culture.